FGF15 Protects Septic Mice by Inhibiting Inflammation and Modulating Treg Responses - Li X; Zhu Z; Xia Z; Xu B (Dove Medical Press, 2022)
Xing Li,1- 3 Zexiang Zhu,3 Zhenkun Xia,4 Bo Xu1,2 1Department of Anesthesiology, The First Clinical College of Southern Medical University, Guangzhou, People's Republic of China; 2Department of Anesthesiology, General Hospital of the Southern Theater Command of the Chinese PLA, Guangzhou, People's Republic of China; 3Department of Critical Care, Changsha of Traditional Chinese Medicine Hospital, Changsha, People's Republic of China; 4Department of Thoracic Surgery, The Second Xiangya Hospital of Central South University, Changsha, People's Republic of ChinaCorrespondence: Bo Xu, Tel +86-18907132861, Email xubo333@hotmail.comBackground: Fibroblast growth factor 15 (FGF15) through its FGF-receptor (FGFR)-4 inhibits hepatic inflammation. The current study aimed at investigating whether FGF15 could inhibit septic inflammation and its compensative regulatory T cell (Treg) responses in a mouse sepsis model of cecal ligation and puncture (CLP) and in vitro transwell co-culture.Methods: Following the sham or CLP procedure, male CLP C57BL/6 mice were intravenously injected with vehicle saline or FGF15 beginning at 2 h post the procedure every 12 h for three days. Some mice were euthanized and their serum and liver samples were collected for examination of cytokines and Tregs by enzyme-linked immunosorbent assay (ELISA), Western blot and flow cytometry. The remaining mice were monitored for their survival up to 14 days post procedure. Moreover, the purified hepatic CD4+ T cells were co-cultured in transwell plates with unmanipulated NCTC 1469 cells or the cells that had been transfected with the control or FGFR4-specific siRNA and treated with, or without, Lipopolysaccharides (LPS) for 24 h, followed by treatment with vehicle PBS or FGF15 for 48 h.Results: Compared with the CLP group of mice, treatment with FGF15 significantly prolonged the mean survival days of mice (12 vs 1.17 in the CLP group, P = 0.022), mitigated hepatic inflammation and reduced the frequency of apoptotic cells in the liver of mice. FGF15 treatment decreased the percentages of hepatic Tregs, hepatic IL-2, TGF-β and FOXP3 expression in septic mice, accompanied by decreasing serum IL-1β, TNF-α, IL-6 and IL-10 levels. Similarly, FGF15 treatment also attenuated the LPS-increased frequency of Tregs, FOXP3 and IL-2 expression and IL-1β, TNF-α, IL-6 and IL-10 secretion in vitro after co-culture with NCTC 1469 cells, but not co-cultured FGFR4-silenced NCTC 1649 cells.Conclusion: FGF15 treatment through FGFR4 ameliorated hepatic inflammation and its compensative Treg responses, which were associated with protecting from septic death in mice.Keywords: FGF15, FGFR4, hepatic inflammation, hepatic Treg infiltrates, septic mice